2016
DOI: 10.1016/j.powtec.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of charge transfer on electrostatic adhesive force under different conditions of particle charge and external electric field

Abstract: The electrostatics of charged particles are utilized for various applications. This paper presents an analysis of the electric field and electrostatic adhesive force on a charged dielectric particle lying on a conducting plane under an externally applied electric field. The purpose of the analysis is to quantitatively investigate the force variation when there is charge transfer between the particle and the conducting plane. We treat the distribution of charges as either uniform on the particle or partially on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…According to Zhao et al's report on the corrosion behaviour of copper in chlorine-containing media, it was explained from the perspective of molecular dynamics that the copper surface became rough over time and copper and chlorine combined in the rough regions [34]. Besides, Boonchai et al studied the effect of charge transfer under applied electric field on the electrostatic adhesion force of charged particles on a conductive plane and found that if the degree of charge transfer changes significantly with the applied field, the external electric field may weaken the electrostatic adhesion [35]. According to the value of the R ct from Table 2 in EIS tests, the increase in the SEF field strength significantly reduced the value of R ct , which indicated to a certain extent that the charge transfer was dependent on the external SEF.…”
Section: Resultsmentioning
confidence: 99%
“…According to Zhao et al's report on the corrosion behaviour of copper in chlorine-containing media, it was explained from the perspective of molecular dynamics that the copper surface became rough over time and copper and chlorine combined in the rough regions [34]. Besides, Boonchai et al studied the effect of charge transfer under applied electric field on the electrostatic adhesion force of charged particles on a conductive plane and found that if the degree of charge transfer changes significantly with the applied field, the external electric field may weaken the electrostatic adhesion [35]. According to the value of the R ct from Table 2 in EIS tests, the increase in the SEF field strength significantly reduced the value of R ct , which indicated to a certain extent that the charge transfer was dependent on the external SEF.…”
Section: Resultsmentioning
confidence: 99%